(3EOGQI GdNUNUI (B:s (3Hjf GdfXQjI h GdJWHjb (B/s - (3YHO GdQMje, RGgQ eMeOs ((3YeGf(B: s (3OGQ GdQGjI(B, s, 2011)
(3GOGQI GdNUNUI h OhQ GdGOGQI GdGSJQGJjLjI aj GdNUNUI , NUNUI h GYGOI Gdgjcd GdJfXjej ddefXeI , GOGQI h JWhjQ GdehGQO GdHTQjI GdYGeI h cjajI NUNUJgG , GdNUNUI h GOGQI GdJZjjQ , GdNUNUI h OhQgG aj GdGUdGM GdGbJUGOj , GdLhOi GdGbJUGOjI h eTQhY GdTQGcI Hjf GdbWGYjf GdYGh h GdNGU , GdeDSSGJ GdYGeI h GdJMhd Gdi GdNUNUI , eXGgQ GdaSGO aj GdNUNUI h cjajI GdMO efgG , GdJNGUjI aj GdOhd GdYQHjI (B.s
Keywords: (3GdGOGQIs; (3GdbWGY GdNGUs; (3GdbWGY GdNGU `` GOGQIs